Buying defence and security in Europe : the EU Defence and Security Procurement Directive in context / Martin Trybus, Professor of European Law and Policy, University of Birmingham. - Trybus, Martin (Cambridge University Press, 2014)
Buying Defence and Security in Europe is the first critical evaluation of the EU Defence and Security Procurement Directive 2009/81/EC, which is now the basis for public and private entities buying armaments and sensitive goods and services in the EU. This instrument aims to ensure non-discrimination, competition and transparency in the security sectors. Part one provides a critical analysis of the economical, historical, political, military-strategic and legal contexts of the new EU Defence and Security Procurement Directive. Part two covers the main aspects of the Directive: its scope, procedures, security of supply and information, offsets and subcontracting, and finally its review and remedies system. This book is an essential overview of a legislative milestone in the field.